Obesity in relation to serum persistent organic pollutant concentrations in CHAMACOS women. Issue 4 (December 2018) - Warner, Marcella; Rauch, Stephen; Coker, Eric S.; Harley, Kim; Kogut, Katherine; Sjödin, Andreas; Eskenazi, Brenda
Abstract : Background: Environmental exposure to endocrine-disrupting chemicals (EDCs), including persistent organic pollutants (POPs), has been hypothesized to increase risk of obesity. Using data from the Center for Health Assessment of Mothers and Children of Salinas (CHAMACOS) study, we examined the longitudinal relationship between serum concentrations of a POPs mixture and several obesity measures. Methods: Concentrations of 17 POPs were measured in serum collected in 2009–2011 from 468 CHAMACOS women. Anthropometry measurements and personal interviews were completed at up to three study visits between 2009 and 2014. We assessed the relationship of serum POPs concentrations with adiposity measures longitudinally using generalized estimation equation (GEE) models. We implemented Bayesian Kernel Machine Regression (BKMR) to elucidate the effects of joint exposure to the POPs mixture. Results: In GEE models, positive associations with body mass index were found for dichlorodiphenyltrichloroethane (Q4 vs. Q1: adjusted β = 3.2 kg/m 2 ; 95% CI = 1.5, 4.9), β-hexachlorocyclohexane (Q4 vs. Q1: adjusted β = 3.6 kg/m 2 ; 95% CI = 2.0, 5.2), and polybrominated diphenyl ether (PBDE)-47 (Q4 vs. Q1: adjusted β = 1.9 kg/m 2 ; 95% CI = 0.3, 3.5), while PBDE-153 was inversely associated (Q4 vs. Q1: adjusted β = −2.8 kg/m 2 ; 95% CI = −4.4, −1.2). BKMR results, while largely consistent with single pollutant models, revealed the shape and direction of the exposure–response relationships, as well as interactions among pollutants within the mixture, that could not be discovered by single-pollutant models. Conclusion: In summary, we found significant associations of serum POPs with several adiposity measures using both conventional regressions and BKMR. Our results provide support for the chemical obesogen hypothesis, that exposure to EDCs may alter risk for later obesity. Abstract : Supplemental Digital Content is available in the text.